Tests and Proofs : 14th International Conference, TAP 2020, Held as Part of STAF 2020, Bergen, Norway, June 22–23, 2020, Proceedings /: 14th International Conference, TAP 2020, Held as Part of STAF 2020, Bergen, Norway, June 22–23, 2020, Proceedings. (2020) - Unknown
No abstract available